EP600 Correlation between preoperative imaging biomarkers and histological prognostic factors in endometrial cancer: a prospective study. (1st November 2019) - Perniola, G; Derme, M; Palaia, I; Musella, A; Di Pinto, A; Santangelo, G; Di Donato, V; Tomao, F; Muzii, L; Benedetti Panici, P
Abstract : Introduction/Background: Endometrial cancer is the most common gynecological malignancy in developed countries. Transvaginal ultrasound (TVUS) and magnetic resonance imaging (MRI) are widely accepted as imaging tools in preoperative local staging. In this prospective study, we evaluated the diagnostic accuracy of TVUS and MRI for detecting the depth of myometrial invasion and cervical involvement and for measuring tumor volume. We also correlated tumor volume to negative histological prognostic factors. Methodology: We enrolled women with a histological diagnosis of endometrial carcinoma. The study was conducted from January 2018 to March 2019. All patients were evaluated by TVUS and pelvic MRI with gadolinium, in the absence of any contraindication. We compared the preoperative imaging results with final histopathology. Results: The mean age was 63, 65±9.79 years. Fifty-four out of the 60 patients resulted suitable for primary surgery. Six patients underwent neoadjuvant chemotherapy for carcinomatosis. Twenty-eight women underwent both TVUS and MRI. The additional 26 patients underwent only TVUS because they were not able to perform MRI. Both TVUS and MRI showed an accuracy of 85.7% for diagnosing presence or absence of myometrial invasion and an accuracy of 100% and 89.3% respectively, for the assessment of deep myometrial infiltration. The accuracy for the cervical involvement was 92.9% and 96.4% for TVUS and MRI respectively. The coefficient of determination (R 2 ) of tumor volume measurement was 0.99, 0.95 and 0.98 using 3-Dimensional (D) TVUS, 2-D TVUS and MRI respectively. A value of tumor volume ≥2 ml showed a positive correlation with negative histological prognostic factors, such as high tumor grade, lymphovascular space involvement (LVSI) and deep myometrial invasion ( p <0.05). Conclusion: The accuracy of TVUS and MRI in evaluating deep myometrial invasion, cervical involvement and tumor volume measurement were comparable. A preoperative evaluation of the tumor volume would allow the identification of the patients with a poor prognosis. Disclosure: Nothing to disclose.